Prototype development of a single step pressure regulation system for the natural gas motorcycle - Mohsin, Rahmat; Yaacob, Zulkefli; Abdul Majid, Zulkifli; Ashraf, Shameed (2005)
The use of Compressed Natural Gas (CNG) for vehicle has proved to improve emission quality, reduces dependency on mainstream fuels and increases lubrication oil lifespan. The successful utilization of ONG on the Kriss Modenas 110cc has been proven by previous researcher. The current study is carried out in the attempt to improve the pressure regulator which is deemed crucial in the CNG fuel system. Various drawbacks of the previously implied unit prove the need for this study. This study begins with a comprehensive understanding of the pressure regulation system. Design considerations are taken and optimized accordingly to enhance the final prototype. The flow within the regulator is optimized using FLUENTâ„¢ while the structural integrity is backed by American Society of Mechanical Engineer (ASME) pressure vessel code and related standards on threaded fasteners. The fabrication of the prototype has been formulated from findings and analysis on the design methodology using suitable machining techniques. The performance of the final prototype is obtained from the specially developed pressure regulator test bench. It is clearly proved that the developed pressure regulator is capable of providing the downstream components with natural gas at 4Bar up to 24liters per minute. This performance is seen constant regardless of the upstream pressure and the downstream flow demand.